Pengaruh Lama Penyemprotan terhadap Kadar Enzim Cholinesterase pada Petani Pengguna Pestisida Organofosfat: The Effect of Spraying Time on Cholinesterase Enzyme Levels in Farmers that Used Organophosphate - Anggi Parasitekta; Purwati Purwati; Tri Harningsih (Jurnal Surya Medika (JSM), 2022)
Pesticides can increase productivity in agriculture. Excessive and uncontrolled use of pesticides can pose a risk of poisoning farmers. Decreased levels of cholinesterase enzymes characterize poisoning. The duration of spraying is an indicator that can affect the levels of the cholinesterase enzyme. This study aimed to determine how long spraying affects cholinesterase enzyme levels in farmers who use organophosphate pesticides. Examination of cholinesterase using the enzymatic cholinesterase test method. The most commonly used sample is a sample of serum rather than red blood cells. The study's results stated that there was a relationship between the duration of spraying and the levels of the cholinesterase enzyme. The duration of spraying in a day gives an idea of ​​the intensity of pesticide exposure. The longer the spraying time, the higher the pesticide exposure and the decreased levels of the cholinesterase enzyme in the blood.